Osteology and Radiographic Anatomy of the Pelvis and Hind Limb of Healthy Ring‐Tailed Lemurs (Lemur catta). (7th May 2013) - Makungu, M.; Groenewald, H. B.; du Plessis, W. M.; Barrows, M.; Koeppel, K. N.
Summary In family Lemuridae, anatomical variations exist. Considering its conservation status (near threatened) and presence of similarities between strepsirrhines and primitive animals, it was thought to be beneficial to describe the gross osteology and radiographic anatomy of the pelvis and hind limb of ring‐tailed lemurs (Lemur catta) as a reference for clinical use and species identification. Radiography was performed in 14 captive adult ring‐tailed lemurs. The radiographic findings were correlated with bone specimens from two adult animals. Additionally, computed tomography of the hind limbs was performed in one animal. The pelvic bone has a well‐developed caudal ventral iliac spine. The patella has a prominent tuberosity on the cranial surface. The first metatarsal bone and digit 1 are markedly stouter than the other metatarsal bones and digits with medial divergence from the rest of the metatarsal bones and digits. Ossicles were seen in the lateral meniscus, inter‐phalangeal joint of digit 1 and in the infrapatellar fat pad. Areas of mineral opacity were seen within the external genitalia, which are believed to be the os penis and os clitoris. Variations exist in the normal osteology and radiographic appearance of the pelvis and hind limb of different animal species. The use of only atlases from domestic cats and dogs for interpretative purposes may be misleading.